A new species of Leptodactylus Fitzinger (Anura, Leptodactylidae) from Serra do Brigadeiro, State of Minas Gerais, Southeastern Brazil - Caramaschi, Ulisses; Feio, Renato N.; São-Pedro, Vinícius A. (Zootaxa, 2008)
A new species of Leptodactylus belonging to the L. fuscus species group, and related to the L. mystaceus complex, is described from the Lagoa das Bromélias (20 o 53’S, 42 o 31’W; 1,227 m above sea level), Parque Estadual da Serra do Brigadeiro, Municipality of Ervália, State of Minas Gerais, Southeastern Brazil. Leptodactylus cupreus sp. nov. is characterized by the large size for the group (SVL 50.1–55.1 mm in males) and color pattern. The new species has a non-pulsed advertisement call, with call rate about 12 calls/s and a dominant frequency between 2,800 and 3,058 Hz.